Domestic urban water rate structure and water prices in Mallorca, Balearic Islands - Angela Hof; Macià Blázquez-Salom; Joana Maria Garau (Boletín de la Asociación de Geógrafos Españoles)
Water rate structures were analysed to assess water prices per unit of water consumed in the domestic urban sector. Water prices and variability are set in spatial context and patterns are analysed on the background of municipal urban and tourist profiles. In addition, scenario calculations reveal that the block rate is not sufficiently progressive and prices are too low, in particular where low density housing with lawns and swimming pools dominates. Finally, we look at the institutional framework for establishing water prices and for managing water resources more sustainably.